An extended short scale for measuring intrinsic motivation when engaged in inquiry-based learning - Manuela Heindl (Journal of Pedagogical Research, 2020)
The aim of this paper was to extend the German multidimensional measurement (KIM) to assess participants' subjective experience related to a target activity. This device consists of: one dimension with three items to test experience-based hypothesising and four dimensions to test intrinsic motivation. The data was gathered in Austria in 2017/18 in various primary schools (age=10 years, n= 677) after an inquiry-based learning lesson. The EFA revealed 15 items were loading on five factors. The reliability (Cronbach's α = .813 and Guttmann split-half coefficient = .834) and the validity (χ2(80) = 123.997; RMSEA = .0029 (90% CI = .018-.0038); CFI = .986; TLI = .982; SRMR = .029) proved significantly a good model fit. The six dimensional questionnaire EKIM can be used to test intrinsic motivation and when engaged in inquiry-based learning in primary schools.